Relative intensity noise of silicon hybrid laser - Hu, Xiao Nan (2014)
We theoretically investigate the relative intensity noise (RIN) of a silicon hybrid laser by taking into account two-dimension transverse modes in the hybrid waveguide. It shows that, when only one transverse mode is excited, RIN spectrum of the hybrid laser exhibits a larger peak value at a lower relaxation oscillation (RO) frequency as compared with the case of a conventional multiple-quantum well (MQW) laser with the the same active region design and dimension. In contrast, when two transverse modes are excited, the hybrid laser shows a lower peak value at a higher RO frequency as compared with the MQW laser. The effects of waveguide dimensions, e.g., Si ridge height and IIII-V ridge width on RIN spectra of the hybrid laser are also investigated.